Witchcraft for wayward girls [large type] - Hendrix, Grady (Random House Large Print, 2025)
"They call them wayward girls. Loose girls. Girls who grew up too fast. And they're sent to Wellwood House in St. Augustine, Florida, where unwed mothers are hidden by their families to have their babies in secret, to give them up for adoption, and most important of all, to forget any of it ever happened. Fifteen-year-old Fern arrives at the home in the sweltering summer of 1970, pregnant, terrified and alone. Under the watchful eye of the stern Miss Wellwood, she meets a dozen other girls in the same predicament. There's Rose, a hippie who insists she's going to find a way to keep her baby and escape to a commune. And Zinnia, a budding musician who plans to marry her baby's father. And Holly, a wisp of a girl, barely fourteen, mute and pregnant by no-one-knows-who. Everything the girls eat, every moment of their waking day, and everything they're allowed to talk about is strictly controlled by adults who claim they know what's best for them. Then Fern meets a librarian who gives her an occult book about witchcraft, and power is in the hands of the girls for the first time in their lives. But power can destroy as easily as it creates, and it's never given freely. There's always a price to be paid...and it's usually paid in blood."--